Case report: successful endoscopic removal of a large rectal foreign body - Bosi, Simone; de'Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2020)
Incidence of emergency access due to retained large rectal foreign bodies is increased in the last years. Such situations are a challenge because often, due to their size and physical characteristics, the large foreign bodies of the rectum cannot be extracted manually or by endoscopy, thus requiring surgery, as reported in the literature.We report a case of a 59-old male with a retention of a large vegetable rectal foreign body (whole eggplant) successfully subjected to endoscopic removal without the need for surgery.